Etiology and Risk Factors Associated with Delayed Development in Preschool Children that Received Treatment in the Developmental Clinic, Roi Et Hospital - Phosri, Nipaphorn (Srinagarind Medical Journal, 2023)
Background and objective: Development in terms of physical, mental, emotional, social, intellectual and growth of preschool children are very important. The purpose of this study was to investigate the etiology and risk factors associated with delayed development in preschool children admitted to the Developmental Clinic of Roi Et Hospital.Methods: The design of this study was a retrospective cohort study. All data were collected from medical records of 156 preschool children with delayed development. All of them were visited at the Roi Et Hospital Developmental Clinic between January 1, 2022 and December 31, 2022. Statistics used for data analysis were descriptive statistics, bivariate analysis and multiple logistical regressions. The statistically significance was set at p-value <0.05.Results: There were 156 cases of delayed development, most of them were male 69.23%, mean aged 22.12±16.47 months 28.85% premature birth. The etiology and risk factors associated with delayed development of gross motor were female, preterm labor, and birth weight <2,500 g. Fine motor were female, preterm labor, birth asphyxia, epilepsy, and cerebral palsy. Language were female, birth weight <2,500 g, cerebral palsy, childhood autism, and history of electronic media used. Personal and social were hypothyroidism, epilepsy, cerebral palsy, and hyperkinetic disorder. Conclusion: This study revealed that factors associated with delayed development of gross motor, fine motor and cognitive skills, language, and personal and social development in pre-school children were gender, preterm birth, birth weight less than 2500 gram, birth asphyxia, cerebral palsy, hyperkinetic disorder, childhood autism , epilepsy, hypothyroidism and regular use of electronic media.